2018
DOI: 10.3390/su10113858
|View full text |Cite
|
Sign up to set email alerts
|

Motivations and Constraints of Meat Avoidance

Abstract: Reducing the consumption of meat can make a significant contribution to sustainable development. However, at least in Western societies with their already rather high levels of per-capita meat consumption, only a minority of consumers reduces meat intake by following a vegetarian or plant-based diet. To arrive at a differentiated understanding of the conditions of meat avoidance, we empirically assess the importance of a broad set of specific motivations and constraints previously discussed in the literature, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 73 publications
3
35
1
Order By: Relevance
“…Overall, the data here support Schenk, Rössel and Scholz's [30] typology of motivations and constraints regarding vegetarian and vegan diets. Health, environmental and ethical aspects are generally rated positively, whilst price, taste and convenience are generally rated negatively.…”
Section: Agreement In Principle Disagreement In Practicesupporting
confidence: 83%
See 4 more Smart Citations
“…Overall, the data here support Schenk, Rössel and Scholz's [30] typology of motivations and constraints regarding vegetarian and vegan diets. Health, environmental and ethical aspects are generally rated positively, whilst price, taste and convenience are generally rated negatively.…”
Section: Agreement In Principle Disagreement In Practicesupporting
confidence: 83%
“…Recent research has identified the major motivations and constraints around vegetarian and vegan diets [30]. The main motivations to move towards a vegetarian or vegan diet are animal welfare, the environment and personal health, whilst the major barriers are sensory enjoyment of animal products, convenience and financial cost [30].…”
Section: Motivations and Constraintsmentioning
confidence: 99%
See 3 more Smart Citations